LIABILITY IN THE CONTEXT OF BLOCKCHAIN-SMART CONTRACT NEXUS: INTRODUCTORY CONSIDERATIONS - Cvetković, Predrag (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Blockchain technology becomes relevant in economic exchange as it lowers costs and adds efficiency to transactions` implementation. The key quality of Blockchain lies in ensuring the authenticity of digital data: trust in the traditional legal relationship has been replaced by digital verification of data in blocks. As the important phenomenon, Blockchain demands legal answers to the issues raised by its implementation. An example of this development is the legal regime of smart contracts. A smart contract is a contract in which any rights and obligations of contracting parties are programmed in a code. Being the result of Blockchain technology application, such a contract is characterized by the need for mutual trust between the contracting parties. As legal phenomenon, Blockchain/smart contract technology raises issue of liability for fulfilment of contractual duties. Smart contracts are able to minimize certain contract risks and additionally simplify contract execution. In addition, the contract implementation does not require any further interaction between the contracting parties. Furthermore, essential components of the smart contract are the digitally verifiable information and the legally relevant actions that the smart contract carries out based on the information received. All of enlisted issues are of importance for proper comprehension of legal liability of Blockchain actors.